2010
DOI: 10.1017/s0033291710000966
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic personality in children: genetic and environmental contributions

Abstract: Background The current study investigates whether the underlying factor structure of psychopathic personality traits found in adults is similar to that in children and what the extent of the genetic and environmental influences are on these psychopathic traits. Method Psychopathic personality traits were assessed in a community sample of 1219 twins and triplets (age 9–10 years) through caregiver reports of each child’s behavior using the Child Psychopathy Scale (CPS). Results Confirmatory factor analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 50 publications
(125 reference statements)
6
105
0
Order By: Relevance
“…Twin studies suggest genetic factors may be more involved in the expression of CP for children high on CU traits than for children low on CU traits [16,17], and shared environmental factors such as parenting were less involved in their CP behaviors [17]. Also, CU traits have been found to relate to temperamental fearlessness [18,19]; this lack of fear may explain why children with CU traits are more difficult to socialize since they fail to experience transgression-related anxiety.…”
Section: Childhood Callous-unemotional Traits Moderate the Relation Bmentioning
confidence: 99%
“…Twin studies suggest genetic factors may be more involved in the expression of CP for children high on CU traits than for children low on CU traits [16,17], and shared environmental factors such as parenting were less involved in their CP behaviors [17]. Also, CU traits have been found to relate to temperamental fearlessness [18,19]; this lack of fear may explain why children with CU traits are more difficult to socialize since they fail to experience transgression-related anxiety.…”
Section: Childhood Callous-unemotional Traits Moderate the Relation Bmentioning
confidence: 99%
“…Forsman et al (2008) reported sex differences in the phenotypic variances for grandiose/manipulative, callous-unemotional (CU), and impulsive/irresponsible traits, but not in the respective contributions of genetic or environmental influences (Forsman et al, 2008). In contrast, Bezdjian et al (2010) reported higher heritability estimates for callous/disinhibited traits and lower heritability estimates for manipulative/deceitful traits in males. Similarly, Fontaine, Rijsdijk, McCrory, and Viding (2010) examined sex differences in the heritability of CU trait trajectories from late childhood to early adolescence and also found evidence for stronger additive genetic influences on CU traits in boys, but only for boys with high or increasing levels of CU traits over time (Fontaine et al, 2010).…”
mentioning
confidence: 96%
“…13,38 In this sample of children, however, there were no sex differences at age 12 years in regard to CU traits. Although sex differences have been noted in the heritability and trajectory of CU traits and psychopathy, 13,39 previous research has not examined potential sex differences in intervention effectiveness on CU traits. [40][41][42] An additional finding of interest was the moderate and positive levels of agreement between CU traits and both dimensional and diagnostic measures of externalizing psychopathology.…”
Section: Discussionmentioning
confidence: 99%